1994
DOI: 10.1007/bf00900964
|View full text |Cite
|
Sign up to set email alerts
|

Rising amyotrophic lateral sclerosis mortality in France 1968?1990: Increased life expectancy and inter-disease competition as an explanation

Abstract: Gompertzian analysis is a statistical technique which has been successfully applied to the analysis of amyotrophic lateral sclerosis (ALS) mortality in England and Wales, Japan and the United States. This paper analyses the consistent trend of rising ALS mortality in France over the years 1968-1990, a period during which crude mortality rose from 400 deaths in 1968 to 950 deaths in 1990. The findings indicate that age-specific mortality rates have risen at ages older than 54 years for men and 53 years for wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…3, 4). Trends in an increasing age at disease onset have also been reported in other countries (11)(12)(13)(14)(15)(16). There are several possible causes of the increase in age at disease onset, one of which is the rising life expectancy observed in the general population.…”
Section: Discussionmentioning
confidence: 74%
“…3, 4). Trends in an increasing age at disease onset have also been reported in other countries (11)(12)(13)(14)(15)(16). There are several possible causes of the increase in age at disease onset, one of which is the rising life expectancy observed in the general population.…”
Section: Discussionmentioning
confidence: 74%
“…That is, people are dying from ALS because they are not dying from other diseases 24 . As therapeutic progress is slow, the social burden due to the disease is bound to increase.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in both incidence and mortality during the last decades has been reported in several surveys [9][10][11][12][13][14][15][16]. This finding has been related to a growing population at risk for the disease because of ageing of the population [1,17], but a true increase in ALS incidence over time cannot be excluded. A previous epidemiological investigation of 230 Neuroepidemiology 2003;22:229-234 Govoni/Granieri/Capone/Manconi/Casetta ALS in the area of Ferrara, northern Italy, carried out by our research group [18] found an incidence rate for the years 1964-1982 which fell into the above-mentioned range of reported rates [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 88%
“…This could be due to changes in lifestyle and behaviour among women who could be more exposed to some factors contributing to the occurrence of the disease than they had been in the past [25]. Otherwise, if the increase in ALS incidence is related to population ageing [1,17], a larger increase in women could be due to a more prominent ageing in the subpopulation of women than the subpopulation of men giving an artifactual increase in incidence in women as compared with men [26]. The official statistics seem to support this explanation.…”
Section: Discussionmentioning
confidence: 99%